Aplikasi Algoritma Pengurutan Menggunakan Java BlueJ Sebagai Media Bantu Pembelajaran - Safni Marwa (Journal of Engineering Science and Technology Management (JES-TM), 2022)
Many research and project development has been done since a decade for algorithm animation. But as fundamental of the programming, sorting algorithm still difficult to understand, especially for the students who were novice or beginner in programming. To cope with that problem, one of the solutions was by creating tool for animation of sorting algorithm. As a teaching aid, this tool could help the students to understand the algorithm and at the end they could be able to build their own program. This research would be developed one of the sorting algorithms techniques that usually use by the lecturer: Merge sort. Java BlueJ will be the IDE (Integrated Development environment) to developed the algorithm animation. The Animation of sorting algorithm would provide the template featuring input random number which could be type by the user or through push the random number buttons, besides import existing data. The process would display visually movement of the bar structures and text where the output would show an ordered bar structure from small to large number. The purpose of the user interface modification was the user convenience to learn algorithm.